PENGARUH KEPEMINPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT BATAVIA PROSPERINDO FINANCE DI SAMARINDA - Darminto Darminto; Edy Humaidy (Jurnal Ekonomi dan Manajemen, 2017)
The Influence of Leadership and Motivation of Employee Performance at PT. Batavia Prosperindo Finance in Samarinda. The purpose of this study is to know and analyze the big is positive, namely: 0.112 the influence of leadership and work motivation on employee performance. Based on the calculation model of this structural equation (inner model) Great 2.421064 bigger than T-table 1,96 and original value sample estimate is positive that is 0,829702, it shows that direction of relationship between leadership with employee performance is positive, which means leadership has a positive and significant impact on the performance of employees of PT. BPF in Samarinda. a questionnaire is assessed by factor loading (Correlation between item score / component score and construct score). Rule of thum used in test of convergence validity of outer loading value> 0,7, AVE> 0,5 and communality. While the discriminant validity test values based on the AVE root comparison for each construct with the correlation between the construct with other constructs in the model and the measurement of cross loading with the construct. Rule of thumb in discriminant validity test for cross loading value> 0.7. The results obtained by the value of cross loading> 0.7 this means it has met the criteria of discriminant validity test. This study also used a model of structural equation (inner model) measured using a dependent construct T-statistic value, the path or pathpoint beta value of T-statistics should be> 1.96 for the two tailed hypothesis. Testing model of structural equation (inner model) in this research using application SmartPLS 2.03 (partial least square). The result of calculation of structural equation model (inner model) Work motivation obtained by T-statistic equal to: 0,332189 smaller than T table 1,96 and original sample estimate value is positive that is: 0,11552 show that relationship between motivation with employee performance is positive. Which means that motive variables work positive but not significant to employee performance PT. BPF in Samarinda. This is due to the motivation has been given to employees have been very good so given the motivation was no longer have a significant effect on employee performance.